Histological assessment and gene expression analysis of intra-oral soft tissue graft donor sites - Stuhr, Sandra (2023)
Aim: To determine the structural and gene expression features of different intra-oral soft tissue donor sites (i.e., anterior palate, posterior palate, maxillary tuberosity and retromolar pad). Materials and Methods: Standardized mucosal tissue punch biopsies were collected from at least one donor site per subject. Histological processing was performed to determine tissue morphometry and quantify collagen composition. Site-specific gene distribution was mapped using targeted gene expression analysis and validated using real time polymerase chain reaction (qPCR). Results: A total of 50 samples from 37 subjects were harvested. Epithelial thickness did not differ between sites. However, lamina propria was thicker in the maxillary tuberosity (2.55 ± 0.92 mm) and retromolar pad (1.98 ± 0.71 mm) than in the lateral palate. Type I collagen was the predominant structural protein in the lamina propria (75.06%–80.21%). Genes involving collagen maturation and extracellular matrix regulation were highly expressed in the maxillary tuberosity and retromolar pad, while lipogenesis-associated genes were markedly expressed in the lateral palate. The retromolar pad showed the most distinct gene expression profile, and the anterior and posterior palate displayed similar transcription profiles. Conclusions: Tissue samples harvested from the anterior and posterior palate differed morphologically from those from the maxillary tuberosity and retromolar pad. Each intra-oral site showed a unique gene expression profile, which might impact their biological behaviour and outcomes of soft tissue augmentation procedures.